Pengaruh Ketaatan Aturan Akuntansi, Kompetensi SDM, Efektivitas Pengendalian Internal dan Good Corporate Governance Terhadap Kecenderungan Kecurangan Akuntansi (Fraud) Pada LPD Se-Kecamatan Kediri, Tabanan - Ni Putu Nensy Aryanti Rahayu; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2022)
The purpose of this study is to find out the influence of compliance with accounting rules, human resources competence, effectiveness of internal control, and good corporate governance against the tendency of accounting fraud (fraud) in LPD Se-Subdistrict KediriTabanan. This research was conducted in all LPD Se-Subdistrict of Tabanan Regency which is still active with a population of 21 LPD with the number of LPD employees 159 people. The research sample is determined by the purposive sampling method, which is a certain criterion, then the number of samples becomes 63 respondents. The data collection technique using questionnaires was then performed multiple liner regression analysis. The results of this study found that the Observance of Accounting Rules affects the tendency of Accounting fraud (fraud). HR competence has no effect on the tendency of Accounting fraud (fraud). The effectiveness of Internal Control affects the tendency of Accounting fraud (fraud). Good Corporate Governance affects the tendency of Accounting fraud (fraud). The advice given is expected to help the Village Credit Institute (LPD) in Kediri sub-district, Tabanan in reducing the tendency of Accounting fraud (fraud) especially in LPD employees.